Correlation Between Gaming Duration in School and Family Environments and Depression Levels in Adolescents using the Apriori Method - Surbakti, Rizky Jonatan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
This study examines the relationship between depression levels in adolescents (aged 14-18 years) and the duration of their online gaming, using the Apriori data analysis method. The main results show a strong correlation between the length of time spent gaming and depression levels. Specifically, it was found that gaming duration is a key factor influencing emotional health. Adolescents who play games (particularly MOBA and Battle Royale genres) in moderation, i.e., 1–2 hours per day, actually exhibit a lower risk of depression and more stable emotional well-being. The aim of this study is to raise awareness among parents, educators, and policymakers about the importance of regulating adolescents' online gaming time to maintain their mental health.